Critical Discourse Analysis of Teun A. Van Dijk's Model on Detik.Com and Kompas.Com News Texts About Citayam Fashion Week - Susanti, Susi; Deliana; Mhd. Pujiono (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
This research discusses critical discourse analysis in Citayam fashion week news in the mass media. The critical discourse analysis used is Teun A. van Dijk's critical discourse analysis seen from the text structure, which consists of 3 structures: macro structure, superstructure and micro structure. Data collection uses listening and note-taking techniques, presenting data using formal and informal methods. This research uses news sources from detik.com and kompas.com. The research results show that Citayam fashion week news on detik.com and kompas.com is seen from a macro structure consisting of thematic and subtopics. Superstructure consisting of title, lead and story. Macro structure consisting of semantics (setting, details, intent and presuppositions), syntax (sentence form: active and passive sentences), coherence: (detik.com "and, that, even so" and Kompas.com "however, because, but"), pronouns: (detik.com and kompas.com use "we, they and he/she"), stylistics (lexicon), rhetorical (graphics: using photos that support the news. Next is rhetorical in detik.com signs quotations and use of bold letters).